اللغة العربية في الجامعات الصينية الحكومية: دراسة تاريخيةArabic Language in Government Universities of China: A Historical Study (Al-Qamar, 2022)
Arabic reached in China through the merchants whose were traders and preachers in same time. Thus, the Arabic flourished in this region widely and many Arabic Scholars served the Arabic language in the field of teaching, learning and translation. Two great nations, Arabic and China, remained formally communication in the field of political, economic and social. The result of this communication, there are 10 Muslim nations out of 56 nations of China. Nowadays there are millions of Muslims in China and 35 hundreds mosques in different cities of China. The movement of Arabic Language strongly continue in China, with the passage of time there were established many departments of Arabic in different universities. These departments are playing important role to flourishing the Arabic language whole the China. Nowadays there are 40 universities of China where the bachelor, master and doctor degree of Arabic Language offering.
Keywords: China; Arabic; Muslim; Mosque; University